Revealing the influence of age and fractional composition of woody biomass on the kinetic characteristics of thermal decomposition - Kapustianskyi, Andrii; Romanova, Kateryna; Galyanchuk, Igor; Yurasova, Oksana (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates processes related to thermal decomposition and direct combustion of woody biomass derived from the fast-growing energy willow Salix fragilis. The task addressed is predetermined by the lack of a sufficient database on kinetic parameters required for the efficient utilization of woody biofuel in modern boiler systems, particularly under conditions of transitioning from fossil to renewable energy sources. The thermal degradation pattern of woody biomass of different ages and particle-size distributions was explored in detail using differential thermogravimetry (DTG) and differential thermal analysis (DTA). The results demonstrate empirical dependences of relative mass loss of samples at heating, which made it possible to identify the characteristic stages of thermal decomposition and the intensity of mass transfer. The clearly observed influence of biomass age and particle-size distribution enabled identification of the key kinetic features that directly affect the combustion rate and completeness of fuel conversion. These differences provide a more accurate prediction of fuel behavior in actual power units and lay the basis for forming the primary database of combustion kinetic constants. The results are attributed to differences in the structural organization of the wood, the biomass age, as well as the content of volatile components in samples of different age groups. The practical application of the established dependences is relevant for the design and optimization of boilers operating on comminuted woody biomass. The defined parameters make it possible to optimize fuel particle-size composition, ensure a rational residence time of biomass particles in the combustion zone, and improve the energy efficiency of boiler units when replacing traditional fuels with renewable raw materials.